Macrophage to neuron communication via extracellular vesicles in neuropathic pain conditions - Francesca Picco; Lynda Zeboudj; Silvia Oggero; Vincenzo Prato; Thomas Burgoyne; Nikita Gamper; Marzia Malcangio (Heliyon)
Neuropathic pain following peripheral nerve injury results from maladaptive changes in neurons and immune cells contribution to mechanisms underlying chronic pain. Specifically, in dorsal root ganglia (DRG), sensory neuron cell bodies release extracellular vesicles (EVs) which promote pro-inflammatory macrophage accumulation that facilitates nociceptive signalling. Here, we show that macrophages shuttle EVs to neurons. Indeed, bone marrow-derived macrophages (BMDMs) release EVs containing microRNA-155 (miR-155) which are taken up by cultured sensory neurons. EV-mediated transfer of miR-155 suppresses phosphatase Ship1 expression and increases cytokine interleukin-6 (IL-6) contents. Intrathecal-injected BMDM-derived EVs accumulate in lumbar DRG and EVs containing miR-155 antagomir result in Ship1 upregulation, Il6 downregulation in neurons in concomitance to attenuation of neuropathic mechanical hypersensitivity. These data suggest that, under neuropathic conditions, pro-inflammatory macrophages shuttle EV-containing miR-155 to neurons and contribute to the expression of pronociceptive IL-6 in DRG.